Komunikasi Kultural dalam Menjaga Kerukunan dan Toleransi di Masyarakat - Khiyaroh, Intiha'ul (Proceedings of Annual Conference for Muslim Scholars, 2024)
This research investigates the cultural communication process surrounding the "tahlilan" tradition in Paciran District, Lamongan Regency, Indonesia. "Tahlilan" is a post-death ritual with varying levels of observance among residents. Some believe individual prayers at home suffice, while others emphasize communal gatherings. The study, employing a phenomenological approach, explores the experiences and perspectives of local communities regarding this tradition. It examines how cultural communication, both verbal and non-verbal, facilitates the implementation of "tahlilan" before and after its execution. Key findings reveal that "tahlilan" plays a crucial role in strengthening social bonds, promoting harmony, and fostering tolerance within the community. Cultural communication between community leaders is vital for understanding and respecting diverse perspectives on this tradition. This research highlights the importance of maintaining a balance between preserving cultural traditions like "tahlilan" and adapting to modern realities. By fostering open communication and mutual understanding, communities can navigate religious and cultural diversity while maintaining social cohesion.